Pengaruh Produktivitas, Profitabilitas, Dan Tingkat Suku Bunga Terhadap Harga Saham - Rafika Chyntia; Yoyon Supriadi; Neni Nurisnaini (Jurnal Ilmiah Manajemen Kesatuan, 2023)
This study aims to determine the Effect of The Activity Ratio, Profitability Ratio and Interest Rate on Stock Prices Case Study on Sub Sector Food and Beverage Companies Listed on the Indonesia Stock Exchange 2015-2020 Period. The population in this study are 26 food and beverage companies listed on the Indonesia Stock Exchange and a total sample of 5 companies with 6 years of data. The sampling method used is a non-random sampling method. The data analysis method used is multiple linear regression analysis to determine the effect of The Activity Ratio, Profitability Ratio and Interest Rate on Stock Prices. Data testing was carried out using IBM SPSS Statistics 25 Software. From the results of the regression analysis test, the t-count value is -895 with a significance level of 0.379 (p > 0.05), then the Total Asset Turnover (X1) variable has no significant effect on stock prices, which means H1 is rejected and then for X2, the t-count value is 2.123 with a significance level of 0.043 (p < 0.05), the Return on Equity (X2) variable has a significant effect on stock prices, which means H2 is accepted then X3 the results of the regression analysis test obtained a t-count value of 2.673 with a significance level of 0.013 (p < 0 0.05) then the variable Interest Rate (X3) has a significant effect on stock prices, which means H3 is accepted Simultaneously, the calculated f value is 4.695 with a significance level of 0.009 (p < 0.05) then the variables are Total Asset Turnover, Return on Equity and Interest Rate has a simultaneous and significant effect on stock prices, which means H4 is accepted. Keywords: Total Asset Turnover, Return on Equity, Interest Rate, Stock Prices